A Window to the World: The long-term effect of Television on Hate Crime - Marek Endrich (University of Hamburg, Institute of Law and Economics (ILE), 2020)
This paper analyzes the long-term impact of television on hate crimes in Germany. In the German Democratic Republic (GDR) foreign television served as a window to the world and exposed viewers to foreign influences. But certain parts of the GDR were excluded from receiving Western television due to geographical features. I argue that this resulted in long-lasting differences in the attitude towards foreigners. Using the spatial variation in signal strength as a natural experiment, the paper tests the effect of Western broadcasts on the rate of hate crimes. Municipalities with no access to foreign broadcasts exhibit a higher degree of xenophobic violence in the period of the migration crisis in Germany between 2014 to 2017. It shows that media can lead to preference changes that persist for a long time after the exposure.
Keywords: J15; K42; 330; hate crimes; refugees; natural experiment; media